The drug recognition guide - Currivan, Mark (Hoboken, New Jersey : Wiley-Blackwell, 2021)
'It is often said that all the really important secrets are ones that are'hidden in plain sight'. This book is designed to make it easier to learn about medication by showing you how to visually deconstruct drug names in ways that reveal the meanings that can lie concealed within them. The importance of medication administration as a health intervention is growing. Demographic changes mean that more people are taking increasing numbers of drugs as part of increasingly complex therapeutic regimes (Royal Pharmaceutical Society, 2016). It has never been more important for all those involved in healthcare to have a thorough grounding in the basics of drug classification. Nursing students have long reported that they find medication management one of the most challenging aspects of their training; and many continue to feel that insufficient time is dedicated to pharmacology in the inevitably crowded pre-registration nursing syllabus (King 2004; Manias 2009; Dilles et al. 2011; Pearson et al. 2018). This book is unlike other books on pharmacology for students. It emerged from a series of clinical tutorials developed for nursing students working and learning on acute hospital wards - on the'front line' so to speak. It was devised by a nursing assessor in response to requests from students to help them become more proficient in drug administration; the students having asked for ways to make it easier for them to identify and classify drugs. The students also asked for help with pronouncing some of the more unpronounceable drug names. This is a common but often overlooked concern. Anxiety about feeling foolish due to mispronouncing drug names can often stop students from asking the sort of questions that they should be asking. This book will help with all of these issues. The book is a directory of drugs, not a formulary; and so it avoids duplicating the functions of the British National Formulary (BNF) (Joint Formulary Committee, 2019) or similar tomes. Consequently, it does not profess to offer guidance to those who prescribe drugs; neither does it catalogue drug dosages, side effects or interactions. Such information is readily available in a host of other books on pharmacology. This book is different. It was tailor made in a format chosen by nursing students to meet particular educational needs identified by nursing students. This helped to ensure that the book's focus remains fixed on drug names and its demystifying and drug-classifying aims'--
Drugs that Affect the Gastrointestinal System -- Drugs that Affect the Cardiovascular System -- Drugs that Affect Blood Coagulation and Lipids -- Drugs that Affect the Respiratory System -- Drugs that Affect the Central and Peripheral Nervous System -- Drugs Used in the Management of Pain -- Drugs Used in the Management of Nausea and Vomiting -- Diabetes Therapy and Other Drugs that Affect the Endocrine System -- Drugs Used to Treat Infectious Diseases -- Chemotherapy and Immunosuppressants.
Includes bibliographical references and index.
Keywords: Pharmaceutical Preparations; Terminology as Topic; Handbook; Nurses Instruction